The Influence of Work Conflict, Workload, and Job Stress on the Turnover Intention of Operational Employees at PT. Nippo Mechantronic Indonesia - Yrasandhi, Tchiska Adri; Sutia, Sabar; Adha, Shultonnyck; Fahlevi, Mochammad (Universitas Mercu Buana, 2025)
The purpose of this study is to examine and determine the influence of work conflict, workload, and job stress on turnover intention, as well as to assess whether these factors affect the turnover intention of operational employees at PT. Nippo Mechantronics Indonesia. Data collection was conducted using a quantitative method and involved 54 respondents. Based on the research findings, the F-test results indicate that the calculated F-value (Fhitung) is 12.668, while the table F-value (Ftabel) is 2.790 at α = 0.05. This finding suggests that work conflict, workload, and job stress simultaneously have a positive and significant effect on turnover intention, leading to the acceptance of hypothesis H4. Partially, the t-test results show that the calculated t-value (thitung) for work conflict is 1.939, while the table t-value (ttabel) is 2.005 with a significance level of 0.086. Since thitung (1.939) < ttabel (2.005) and significance (0.086) > 0.05, work conflict does not have a partial effect on turnover intention, resulting in the rejection of hypothesis H1. Similarly, for workload, the calculated t-value (thitung) is 1.635, while the table t-value (ttabel) is 2.005, with a significance level of 0.108. Since thitung (1.635) < ttabel (2.005) and significance (0.108) > 0.05, workload does not have a partial effect on turnover intention, leading to the rejection of hypothesis H2. However, for job stress, the calculated t-value (thitung) is 2.577, while the table t-value (ttabel) is 2.005, with a significance level of 0.013. Since thitung (2.577) > ttabel (2.005) and significance (0.013) < 0.05, job stress has a positive and significant partial effect on the turnover intention of employees at PT. Nippo Mechantronics Indonesia, resulting in the acceptance of hypothesis H3.The adjusted R-square value of 0.432 represents the coefficient of determination, meaning that 43.2% of turnover intention can be explained by work conflict, workload, and job stress.